ENGLISH ADJECTIVES AS FOUND IN THE NOVEL THE OLD MAN AND THE SEA - Bonar Gurning; Fretty R. Lumban Gaol (Muse: Jurnal of Art, 2024)
This study deals with English adjectives as found in the novel The Old Man and the Sea written by Ernest Hemingway. In this study, the writers examined the functions of adjectives and types of adjectives which are found in the novel by applying the theories proposed by Quirk et al (1985) and Vikas (2003). In this study, the writers found that the predicative adjectives consisting of 239 data are more productive than the attributive adjectives consisting of 75 data. Dealing with types, the most productive type is quality adjective (59.23%) followed by quantity adjectives (14.33%), possessive adjectives (8,28%), interrogative adjectives (5,73%), articles (5,41%), distributive adjectives (2.87%), emphasizing adjectives (2.87%),and demonstrative adjectives (1.59%).